PENERAPAN E-COMMERCE PADA PENJUALAN BOUQUET BUNGA DAN PAPAN AKRILIK - Siregar, Regita Yori; Siregar, Fairuz Azzaria; Rahma, Najahaura; Sintiya, Aqilla; Batubara, Nabila Rahmadani (Insan Pembangunan Sistem Informasi dan Komputer (IPSIKOM), 2024)
E-commerce is a method of selling and purchasing goods and services over the Internet. E-commerce is part of e-business, and refers to a broader scope. Not only buying and selling transactions, but also collaboration with business partners, customer service, human resource recruitment, and so on. Apart from web network technology, electronic commerce also requires other non- computer based technologies such as database technology, electronic mail (email), product delivery systems, and payment methods. The opportunities for e-commerce in the business world are still very large, especially in Indonesia, considering that the available market is still wide open. This research aims to develop an E-commerce system that facilitates the sale and ordering of Flower Bouquets and Acrylic Boards, complete with detailed product information and ordering guides. This e-commerce system was built using the HTML and PHP programming languages, as well as Bootstrap to beautify the appearance. It can be concluded that the resulting system is able to simplify the sales process, convey product information, and the product ordering process according to consumer wishes.Keywords:e-commerce, market place, HTML, PHP,Bootstrap